(untitled) (Discourse of Law and Administration, 2023)
The paper focuses on the status of public administration, which is increasingly taking over the competences of other authorities in providing basic security for citizens. The issue here are not violations of the constitution or laws, which need to be discussed separately, but to point out that, even with formal respect for the separation of powers, we are facing profound changes that must be resilient to the state crisis. The recent accumulation of the policy of force points to a threat to the existing paradigm of public administration, and academic reflection and analysis of legal norms do not always sufficiently capture the danger of another world war. The study draws conclusions on the greatest dangers to firmly maintaining the systemic foundations of the separation of powers in a democratic state of law. The main dysfunctions in the development of the Ukrainian public administration, forced to choose between freedom and sovereignty and the lives of its citizens, were also identified. In this context, the issues of information policy and the consequences of the rapid development of information technology using the destruction of the population according to the so-called “Syrian model” are also shown. Due to the dynamics of the warfare and the impossibility to verify much of the information at the scene, the author relied heavily on films posted on the internet, information presented by the Ukrainian authorities and information from the war refugees themselves. Some of the information has been compiled from US Department of Defence (Pentagon) press releases.